IMPLEMENTATION OF DISTRIBUTED AVERAGE CONSENSUS METHOD ON WIRELESS SENSOR NETWORK FOR MONITORING TEMPERATURE AND HUMIDITY IN SWITCHGEAR ROOM - Putro, Mohamad Tri Azis Budi Cahyono (Jurusan Teknik Elektro Fakultas Teknik UNESA, 2021)
The development of wireless sensor networks is currently very rapid in various sectors. One of the implementations of the wireless sensor network is for monitoring temperature and humidity. In monitoring a room or a large area, many nodes are installed at a certain point. With the number of senses by each node so that one data that can represent the area is needed. To get one data that can represent the data in that area, we need a consensus method. In this study, the average distributed consensus method was used to obtain data representation from an area's wireless sensor network. After testing and simulating the ideal range between WSN nodes is 30 meters where the average percentage of detection errors reaches 0%. And the maximum capability is 33 meters with an average percentage of error detection of 46%. If given a barrier between WSN nodes, the distance that can be reached becomes shorter, with an ideal distance of 16 meters with an average percentage of error detection of 0% and the farthest distance reaching 21 meters with a detection error of 50%. The results of the consensus method simulation show that the more slots are filled with consensus data about the results, the faster and easier convergence will be achieved, in this case the monitoring results represent the real situation.